Measuring instructors continued intention to reuse Google Classroom in Iraq: a mixed-method study during COVID-19 - Hussein M.H.; Ow S.H.; Ibrahim I.; Mahmoud M.A. (Emerald Group Holdings Ltd., 2024)
Indexed by WOS/Scopus/ERA